2005
DOI: 10.1159/000083451
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cytokines and Chemokines on Sickle Neutrophil Adhesion to Fibronectin

Abstract: A role for leukocytes in sickle cell vaso-occlusive crisis is becoming increasingly recognized. Neutrophil counts are higher in sickle cell patients and neutrophils from these patients demonstrate increased adhesion to endothelial monolayers under certain circumstances. The effects of selected cytokines on the adhesion mechanisms of normal neutrophils and neutrophils from sickle cell anaemia patients (SCA neutrophils) were investigated. Neutrophils were separated from the blood of homozygous (HbSS) SCA patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
11

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 46 publications
1
37
0
11
Order By: Relevance
“…It has been shown that the adhesive molecules involved in increased adhesiveness of granulocytes and monocytes and leukocytes interaction with endothelial cells are the cytokine-induced L-and P-selectin (CD-62L), β2-integrin CD11b/C18 (CD-11b) and LFA-1 (CD11a/CD18) [49][50][51][52]. L-selectin (CD62L) facilitates rolling and temporary arrest of circulating leukocytes on endothelium surface [53], whereas β2-integrin (CD11b) is involved in subsequent stable adhesion [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the adhesive molecules involved in increased adhesiveness of granulocytes and monocytes and leukocytes interaction with endothelial cells are the cytokine-induced L-and P-selectin (CD-62L), β2-integrin CD11b/C18 (CD-11b) and LFA-1 (CD11a/CD18) [49][50][51][52]. L-selectin (CD62L) facilitates rolling and temporary arrest of circulating leukocytes on endothelium surface [53], whereas β2-integrin (CD11b) is involved in subsequent stable adhesion [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…A ativação dos monócitos, com a secreção de citocinas pró-inflamatórias (IL-1 e TNF-α), leva os leucócitos, em número constantemente elevado, a aderirem ao endotélio inflamado e a interagirem com as hemácias falcizadas [44][45][46][47][48][49] .…”
Section: As Doenças Falciformesunclassified
“…The recruitment of large, less deformable, adherent white cells to the vascular endothelium and their interaction with circulating erythrocytes may impair blood flow. SCA neutrophils differ from those of healthy individuals, as exemplified by their enhanced adhesion to fibronectin and increased spontaneous and chemokine-stimulated chemotaxis in vitro (Assis et al, 2005;Canalli et al, 2007). In SCA, neutrophils overexpress a variety of adhesion molecules on their surface that are involved in cell adhesion and transendothelial migration (Canalli et al, 2011).…”
mentioning
confidence: 99%